Pengaruh Teknologi Artificial Intelligence berupa ChatGPT dalam Pengembangan Sumber Daya Manusia - Andiniatul Maulidia; Elina Zahrotul Firdaus; Muhammad Alkirom Wildan (JURNAL RISET MANAJEMEN (JURMA), 2024)
This research aims to analyze the use of Artificial Intelligence (AI) technology, specifically ChatGPT, in improving Human Resources (HR) skills and competencies. The main focus of this research is to identify the role of ChatGPT in HR training and development, including the improvement of communication skills, problem solving, and continuous learning through AI-based interactions. The research method used was descriptive quantitative, with data collection through questionnaires involving 58 students from various universities in East Java. The results showed that the majority of students reported significant benefits from the implementation of ChatGPT, which not only enriched the learning experience but also improved in-depth and interactive understanding of the material. The findings provide important insights for educational institutions in developing strategies to increase the adoption of AI technology in supporting students' learning process.